2022
DOI: 10.1123/iscj.2020-0092
|View full text |Cite
|
Sign up to set email alerts
|

Examining Experienced S&C Coaches’ Reflections on the Effectiveness of Psychosocial Behaviors in Coaching

Abstract: This study aimed to examine elite, experienced strength and conditioning (S&C) coaches’ reflections on the effectiveness of psychosocial behaviors in S&C coaching. In particular, this study aimed to explore which psychosocial behaviors are essential, the process of how these might influence coaching practice, and how the development of psychosocial behaviors should be encouraged. Eight elite, experienced S&C coaches were recruited and partook in a semistructured interview. Using a reflexive themati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…For example, professional golfers believe that their personal life strongly affects their tournament performance [33]. Building on this, HLCs in this study believed that trust, care, role modelling, and authenticity are essential psychosocial behaviours for developing effective relationships with athletes [22].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, professional golfers believe that their personal life strongly affects their tournament performance [33]. Building on this, HLCs in this study believed that trust, care, role modelling, and authenticity are essential psychosocial behaviours for developing effective relationships with athletes [22].…”
Section: Discussionmentioning
confidence: 91%
“…This lack of focus on various S and C training methods and their effectiveness places a limitation on the impact SCCs can ultimately achieve. Recently, Szedlak et al [22] used semistructured interviews to explore which psychosocial actions experienced SCCs believed to be essential and advocated a constructivist learning approach in order to develop these behaviours. Although this emergent psychosocial direction of research adds much-needed variance to the predominance of biophysical competency, more examination is needed regarding the cognitive development of SCCs.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of research in the field of strength and conditioning (S & C) directed towards identifying the behavioural, knowledge-related and psycho-social characteristics of SCCs with different levels of experience. Much of this research has been achieved by focusing on perceptions of SCCs and athletes, using both semi-structured interviews (Szedlak et al, 2015;Szedlak et al, 2021) and surveys (LaPlaca & Schempp, 2020). Importantly, however, while this research is valuable in developing a better understanding of what, how and whom to coach in S&C environments, there remains a paucity of investigations concerning the decision-making characteristics and processes of SCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst there is existing research identifying the effective coaching behaviours of experienced SCCs (LaPlaca & Schempp, 2020;Gillham et al, 2016;Tod et al, 2012;Szedlak et al, 2015) less is known about the characteristics of less experienced SCCs (Carson et al, 2021;Laplaca & Schempp, 2020). Research within S & C has highlighted the importance of interpersonal skills (Szedlak et al, 2021;Szedlak et al, 2019) with increased skills reported to distinguish between expert and competent SCCs (LaPlaca & Schempp, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, knowledge on what and how to deliver is important for SCCs, but the cognitive characteristics (underpinning the why/why not) of DM for SCCs must not be overlooked. Encouragingly, research focusing on accessing the psychosocial knowledge of SCCs is also beginning to emerge [3,4], although methodologies employed have so far seemed rudimentary.…”
Section: Introductionmentioning
confidence: 99%